Behind a closed door - Barker, J. D. (Jonathan Dylan), 1971- (Hampton Creek Press, 2023)
Sugar & Spice is the latest app craze taking the world by storm, but for Abby and Brendan Hollander, downloading it leads to a dangerous game of life and death. When the app assigns them a series of increasingly taboo tasks, they soon find themselves caught up in a twisted web of seduction and violence.